Left ventricular non‐compaction revealed by aortic regurgitation due to Kawasaki disease in a boy with LDB3 mutation. Issue 8 (23rd August 2016) - Hachiya, Akira; Motoki, Noriko; Akazawa, Yohei; Matsuzaki, Satoshi; Hirono, Keiichi; Hata, Yukiko; Nishida, Naoki; Ichida, Fukiko; Koike, Kenichi
Abstract: Kawasaki disease (KD) is an acute febrile illness of childhood characterized by systemic vasculitis, especially coronary arteritis. Aortic valve regurgitation (AVR) is a relatively common complication. There have been no reports to date of heart failure and left ventricular non‐compaction (LVNC) after acute KD, although the precise etiology of this condition remains unclear. A 6‐month‐old boy with KD was admitted to hospital. Despite high‐dose i.v. gammaglobulin for dilation of the coronary artery, moderate AVR appeared, and thereafter he developed heart failure. A rough, dense LV myocardium indicated LVNC. On genetic testing a heterogenous 163G > A substitution changing a valine to isoleucine in LIM domain binding protein 3 ( LDB3 ) was identified. Additional cardiac stress, such as that caused by AVR and/or KD might have triggered cardiac failure in the form of LVNC due to LDB3 mutation.